THE EFFECT OF MENTHA PIPERITA (L.) EXTRACT DIETON TOTAL WHITE BLOOD CELL, PHAGOCYTE COUNTS AND DISEASE RESISTANCE AGAINST EDWARDSIELLA TARDA IN ROHU (LABEO ROHITA HAM.) FINGERLINGS - Thuy, Nguyen Thi Thanh (Vietnam Journal of Marine Science and Technology, 2007)
Rohu fingerlings (Labeo rohita Ham.) were fed on normal diet and treated groups were fed on plant Mentha piperita (L.) extract diet with varying doses of 10, 20 and 30 ml/100 g feed. After three weeks of feeding, blood was collected from all the groups for testing of total white blood cell (WBC) and phagocyte counts. Then all fish group were immunized and challenged with Edwardsiella rarda. Results indicated that there was no significant difference (P > 0.05) in total WBC count between the control and plant extract treated fish groups. However, the phagocytes and disease resistance against E. rarda significantly (P < 0.05) increased in the plant extract treated fish. The total WBC count significantly (P < 0.05) increased in the treated groups fed on the diet or 20 and 30 ml/100 g reed after immunization